(untitled) (Applied Biological Research, 2023)
Alkaline proteases have high commercial value as these are used in a variety of industrial sectors. In present study alkaline protease was isolated from several acillus species isolated from the rhizosphere of Poaceae plants and then purified. On the basis of morpho-biochemicalcharacteristics, five Bacillus species viz., B. amyloliquefaciens, B. licheniformis, B. pumilis, B. cereus, and B. subtilis were identified. The maximum protease activity was recorded in 1-5 dilution. B. licheniformis exhibited stable activity of 1.09 ± 0.09 U mg-1. Dialysis and ammonium sulphate precipitation methods were used for partial purification. At each stage of purification, protease assay, protein concentration, and specific activity were determined. Among the isolated Bacillus species, B. licheniformis showed a sustained specific activity of 0.47 ± 0.02 mol-1 min-1 mg-1 in crude form, which rose to 0.71 ± 0.02 mol-1 min-1 mg-1following salt precipitation, and reached a high level of 1.02 ± 0.08 mol-1 min-1 mg-1 after dialysis. The physical immobilization of proteases in sodium alginate showed satisfactory activity and stability for B. licheniformis (1.4 ± 0.2 U mg-1). B. licheniformis was sequenced and its phylogenetic tree constructed. The bacterium shared common ancestor with other five distinct Bacillus species. The study revealed that B. licheniformis has potential alkaline proteases production ability.